Chemical resistance of thermosets - Baur, Erwin; Ruhrberg, Katja; Woishnis, William, 1958- (Elsevier : William Andrew, 2018)
Annotation 'Chemical Resistance of Commodity Thermosets' provides a comprehensive, cross-referenced compilation of chemical resistance data that explains the effect of thousands of reagents, the environment and other exposure media on the properties and characteristics of thermosets - plastics which are used in a range of applications. Specifically, the resistance data in this book covers the following materials, allyl, epoxy, unsaturated polyester resin, unsaturated polyurethane resin, vinyl ester resin, furan resin, polyaminobismaleimide, acrylics, polycyanurates and filled/reinforced thermosets.
Includes index.
Keywords: Thermoplastics -- Chemical resistance.; elektronické knihy; electronic books